2016
DOI: 10.1038/srep24099
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore biosynthesis coordinately modulated the virulence-associated interactive metabolome of uropathogenic Escherichia coli and human urine

Abstract: Uropathogenic Escherichia coli (UPEC) growth in women’s bladders during urinary tract infection (UTI) incurs substantial chemical exchange, termed the “interactive metabolome”, which primarily accounts for the metabolic costs (utilized metabolome) and metabolic donations (excreted metabolome) between UPEC and human urine. Here, we attempted to identify the individualized interactive metabolome between UPEC and human urine. We were able to distinguish UPEC from non-UPEC by employing a combination of metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…These strains were found to influence the metabolome, which differentiated pathogenic and non‐pathogenic strains . It was found that the metabolomes of the pathogenic strains with genetic deletions of the enzymes that regulate these metabolites were similar to non‐pathogenic strains, thus revealing these metabolites as key determinants of urinary tract infections …”
Section: Understand Biological Impact Of Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These strains were found to influence the metabolome, which differentiated pathogenic and non‐pathogenic strains . It was found that the metabolomes of the pathogenic strains with genetic deletions of the enzymes that regulate these metabolites were similar to non‐pathogenic strains, thus revealing these metabolites as key determinants of urinary tract infections …”
Section: Understand Biological Impact Of Metabolomicsmentioning
confidence: 99%
“…15 It was found that the metabolomes of the pathogenic strains with genetic deletions of the enzymes that regulate these metabolites were similar to non-pathogenic strains, thus revealing these metabolites as key determinants of urinary tract infections. 151 MicroRNAs (miRNAs) regulate the metabolic reprogram in cancer and metabolic disorders. [152][153][154] Because individual miRNA potentially regulate hundreds of proteins and metabolites, a large-scale coupling of miRNA profiles with metabolomics allows the miRNA-metabolite relationships to be mapped in a high-throughput manner.…”
Section: Genetic Manipulation To Reveal Metabolome Regulationmentioning
confidence: 99%
“…However, the disease is predominantly caused by Uropathogenic E. coli (UPEC; Schulz, 2011; Flores-Mireles et al, 2015; Su et al, 2016b), which accounts for up to 75% of all cases (Foxman, 2002, 2003; Martinez and Hultgren, 2002) and 95% of community-acquired cases (Kucheria et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that Ent-Cipro, a synthetic siderophore-antibiotic conjugate based on the native Ent (enterobactin, a kind of siderophore) platform affords targeted antibacterial activity against Escherichia coli strains that express the pathogen-associated IroA gene cluster (Neumann et al, 2018). Furthermore, yersiniabactin and salmochelin produced by E. coli strains have been proven to cause infection in UTIs by previous experiments, and lead to new antibiotics against these two siderophores as a potential strategy to prevent and treat UTIs (Henderson et al, 2009;Su et al, 2016;Ohlemacher et al, 2017). Furthermore, Rakin et al (2012) demonstrated that there are several siderophore iron-scavenging systems apart from Ybt in another highly virulent genus-Yersinia.…”
Section: Innovative Applications Of Siderophores In Deciphering Tmentioning
confidence: 99%
“…Specifically, different types of mass spectrometry, such as inductively coupled plasma-mass spectrometry (ICP-MS), matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), electrospray-ionization mass spectrometry (ESI-MS), affinity selection-mass spectrometry (ASMS), laser ablation electrospray ionization-mass spectrometry (LAESI-MS), and mass spectrometry imaging (MSI) techniques (MALDI-MS imaging and DESI-MS imaging), have been broadly used to identify siderophores (Pluhacek et al, 2016;Su et al, 2016;Hagan et al, 2017;Walker et al, 2017). In short, mass spectrometry and associated technologies are emerging as novel tools for the annotation of chemical, biological, and biomedical applications of pathogen-associated siderophores.…”
Section: Innovative Applications Of Siderophores In Deciphering Tmentioning
confidence: 99%